Rethinking disadvantage: A social capital approach to widening participation. (1st April 2020) - Johnson, Matthew; Bowden, Gareth; Alonso, Guillermo
In England and Wales, the introduction of ?9, 250 higher education (HE) tuition fees and concern more broadly about social mobility has led to the creation of a series of initiatives aimed at widening participation (WP). Increasingly, critics argue that these initiatives have failed to achieve genuine representativeness, with lower ranked universities absorbing higher numbers of students from underrepresented groups, who then face additional challenges in securing progression to employment. In this article, we examine dominant narratives in WP programmes in England and Wales in order to assert means of widening access more effectively, in the first instance, but also retention and progression. Rejecting non-subject-specific instrumental approaches that focus directly on graduate labour market value and earnings, we argue that effective WP ought to focus centrally on the institutional value of HE and on fostering social capital, especially in lower ranked universities whose graduates are already discriminated against in the labour market. To this end, we evaluate the deployment of a politics-based WP programme, Rethinking Disadvantage, asserting a set of conclusions for colleagues in other disciplines and institutions who seek to develop their own approaches.